Motivated Shield From Chronic Noise Environment: Moderation of the Relationship Between Noise Sensitivity and Work Wellbeing by Need for Closure - Livi, Stefano; Pica, Gennaro; Carrus, Giuseppe; Rullo, Marika; Gentile, Marta (Frontiers in Psychology, 2018)
Several studies have underlined how chronic exposure to environmental noise may have negative effects on performance, wellbeing, and social relations. The present study (N = 90 employees of a motor factory who are chronically exposed to environmental noise) investigated whether the negative effects of chronic exposure of noise-sensitive individuals to noise in the workplace may be moderated by the need for cognitive closure (i.e., an epistemic tendency to reduce uncertainty; NFCC, Kruglanski, 2004). As NFCC has been shown to enhance protection of the focal goal by reducing interference (Kossowska, 2007; Pica et al., 2013), we hypothesized that people with high NFCC should be able to manage the interference coming from environmental noise and concentrate on their tasks more than their low-NFCC counterparts. The results confirm that the negative effects of noise sensitivity on job satisfaction, state anxiety, and turnover intent were higher among low (vs. high)-NFCC individuals.